Single Cell Dissection of Epithelial-Immune Cellular Interplay in Acute Kidney Injury Microenvironment - Zhang, Min; Wu, Lingling; Deng, Yiyao; Peng, Fei; Wang, Tiantian; Zhao, Yinghua; Chen, Pu; Liu, Jiaona; Cai, Guangyan; Wang, Liqiang; Wu, Jie; Chen, Xiangmei (Frontiers in Immunology, 2022)
Abstract Background: Understanding the acute kidney injury (AKI) microenvironment changes, and the complex cellular interaction is essential to elucidate the mechanisms and develop new targeted therapies for AKI. Methods: We employed unbiased single-cell RNA sequencing to systematically resolve the cellular atlas of kidney tissue samples from mice at 1, 2 and 3 days after ischemia-reperfusion AKI and healthy control. The single-cell transcriptome findings were validated using multiplex immunostaining, western blotting, and functional experiments. Results: We constructed a systematic single-cell transcriptome atlas covering different AKI timepoints with immune cell infiltration increasing with AKI progression. Three pre-injured (pi) proximal tubule cells (PTCs) subtypes (pi-PTC-S1/S2/S3) were identified, with upregulation of injury and repair-regulated signatures such as Sox9, Vcam1, Egr1, and Klf6 while with downregulation of metabolism. pi-PTC-S1 exhibited pro-inflammatory and pro-fibrotic signature compared to normal PTC and trajectory analysis revealed that proliferating PTCs were precursor cell of pi-PTC-S1, and part of pi-PTC-S1 cells may turn into PTC-injured and then become fibrotic. Cellular interaction analysis revealed that pi-PTC-S1 and PTC-injured interacted closely with infiltrating immune cells through CXCL and TNF signaling pathway. Immunostaining validated that injured PTCs expressed high level of TNFRSF1A and Kim-1, functional experiments revealed that exogenous addition of TNF-α promoted kidney inflammation and injury dramatically and specific depletion of TNFRSF1A would abrogate the injury. Conclusions: The single-cell profiling of AKI microenvironment provides new insight for deep understanding of molecular changes of AKI, and benefits elucidating the mechanisms and developing new targeted therapies for AKI.